A giant urethral stone with urethrocutaneous fistula: A case report - Henry Pramana; Jupiter Sibarani (Urology Case Reports)
Calculi in the urethra are uncommon, and urethral calculi causing urethrocutaneous fistula are extremely rare. A 56 years-old man with history of urine passage from his scrotal area for a month. During physical examination, we found a multiple fistula in scrotal area and revealed by the ultrasound. Abdominal x-ray suggests a vesicolithiasis and multiple urethrolithiasis. To date, there are 14 cases of giant urethral stone with and without urethrocutaneous fistula reported in literature worldwide for the last 14 years. It was related to patients that delayed to seek a medical attention from his symptoms.